Increasing Teachers' Creativity Through Strengthening Organizational Culture and Achievement Motivation - Nono Yatno; Rita Retnowati; Suhendra Suhendra (Peneliti.net, 2025)
Teacher creativity is an important factor in improving the quality of learning and the quality of education. This study aims to analyze the influence of organizational culture and achievement motivation on teacher creativity. The study used a quantitative approach with a survey method of 150 public elementary school teachers in Depok City. Data were collected using a Likert scale questionnaire and analyzed using path analysis. The results of the study show that organizational culture and motivation for achievement have a positive and significant effect on teachers' creativity. In addition, organizational culture also has a positive effect on motivation to achieve. These findings show that increasing teacher creativity can be done through strengthening a conducive organizational culture and increasing motivation to excel